The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1198/jasa.2011.tm10276
|View full text |Cite
|
Sign up to set email alerts
|

Large Volatility Matrix Inference via Combining Low-Frequency and High-Frequency Approaches

Abstract: It is increasingly important in financial economics to estimate volatilities of asset returns. However most the available methods are not directly applicable when the number of assets involved is large, due to the lack of accuracy in estimating high dimensional matrices. Therefore it is pertinent to reduce the effective size of volatility matrices in order to produce adequate estimates and forecasts. Furthermore, since high-frequency financial data for different assets are typically not recorded at the same ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 22 publications
0
69
0
1
Order By: Relevance
“…This estimation procedure has been used for one-regime factor models with stationary processes in Tao et al (2011) andBathia (2011), and with nonstationary processes in Chang, Guo, and Yao (2013). Many numerical results show that the estimation of the loading space is not sensitive to the choice of l 0 ; see Lam, Yao, and Bathia (2011), Lam and Yao (2012), and Chang, Guo, and Yao (2013.…”
Section: Estimation Of B K µ K D and The Transition Probabilitiesmentioning
confidence: 99%
“…This estimation procedure has been used for one-regime factor models with stationary processes in Tao et al (2011) andBathia (2011), and with nonstationary processes in Chang, Guo, and Yao (2013). Many numerical results show that the estimation of the loading space is not sensitive to the choice of l 0 ; see Lam, Yao, and Bathia (2011), Lam and Yao (2012), and Chang, Guo, and Yao (2013.…”
Section: Estimation Of B K µ K D and The Transition Probabilitiesmentioning
confidence: 99%
“…We can also estimate Σ ζζ byΣ ζζ =Â ΣÂ . Tao et al (2011) showed the consistency ofB andΩ t for fixed k, under several kinds of realized covariance matrices developed by Barndorff-Nielsen et al (2008, 2011), Christensen, Kinnebrock, and Podolskij (2010, Griffin and Oomen (2011), Hautsch, Kyj, and Oomen (2012), Wong and Zou (2010 and Zhang (2011). It is straightforward to show the consistency ofφ t andΣ ζζ by applying the framework of Tao et al…”
Section: Estimation Of Factor Covariancementioning
confidence: 95%
“…By using the sequence of realized covariance matrix, Tao et al (2011) developed a technique to estimate the factor covariance matrix, Ω t . We will shortly explain the approach.…”
Section: Estimation Of Factor Covariancementioning
confidence: 99%
“…The approach by Tao et al (2011) and extensions in Shen et al (2015) and Asai & McAleer (2015) decompose the RCOV matrix in a similar fashion to Engle et al (1990). Asai & McAleer (2015) model the decomposed factor in a number of ways including time-series models with long-memory, asymmetric effects and as a conditional autoregressive Wishart model.…”
Section: Introductionmentioning
confidence: 99%